Two novel SUCLA2 variants cause mitochondrial DNA depletion syndrome, type 5 in two siblings - Zhang, Xiaohuan; Zhang, Guo; Cao, Li; Zhou, Wenjing; Tan, Chang; Ma, Shi; Yang, Jiyun (Frontiers in Neurology, 2024)
Mitochondrial DNA depletion syndrome (MDS), characterized by succinate-CoA ligase deficiency and loss of mitochondrial DNA (mtDNA), is caused by specific variants in nuclear genes responsible for mtDNA maintenance. SUCLA2-related mitochondrial DNA depletion syndrome, type 5 (MTDPS-5), presents as a rare, severe early progressive encephalomyopathy. This report investigates a new family exhibiting clinical manifestations of MTDPS-5 and elucidates the genetic basis of this disorder. In two affected siblings, a novel maternally inherited nonsense variant [c.1234C>T (p.Arg412*)] in the SUCLA2 gene and a unique paternally inherited indel variant (g.48569263–48571020del1758insATGA) were identified. Additionally, the siblings exhibited blood mtDNA content lower than 33% compared to age-matched controls. These findings underscore the importance of assessing SUCLA2 variants in patients with severe early progressive encephalomyopathy, even in the absence of methylmalonic aciduria or mtDNA loss, thereby broaden the mutational spectrum of this gene.